The effect of supplier industry competition on pay-for-performance incentive intensity - Carter, Mary Ellen; Choi, Jen; Sedatole, Karen L. (Journal of Accounting and Economics, 2021)
We examine how supplier industry competition affects CEO incentive intensity in procuring firms. Using Bureau of Economic Analysis data to compute a weighted supplier industry competition measure, we predict and find that higher supplier competition is associated with stronger CEO pay-for-performance incentive intensity. This effect is incremental to that of the firm's own industry competition previously documented and is robust to alternative measures of supplier competition and to exogenous shocks to competition. Importantly, we show that performance risk and product margin act as mediating variables in the relation between supplier competition and CEO incentive intensity providing support for the theory underpinning our finding. We document that CEO compensation contracts are used as a mechanism to exploit the market dynamics of upstream industries to a firm's benefit. Our findings are economically important as suppliers provide, on average, 45 percent of the value delivered by procuring firms to the market (BEA, 2016).